2011
DOI: 10.1038/bjc.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

The tumour-suppressive function of miR-1 and miR-133a targeting TAGLN2 in bladder cancer

Abstract: Background:On the base of the microRNA (miRNA) expression signature of bladder cancer (BC), we found that miR-1 and miR-133a were significantly downregulated in BC. In this study, we focussed on the functional significance of miR-1 and miR-133a in BC cell lines and identified a molecular network of these miRNAs.Methods and results:We investigated the miRNA expression signature of BC clinical specimens and identified several downregulated miRNAs (miR-133a, miR-204, miR-1, miR-139-5p, and miR-370). MiR-1 and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
286
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(312 citation statements)
references
References 38 publications
24
286
2
Order By: Relevance
“…Interleukin-6 treatment downregulates miR-370 expression, while 5-aza-dC upregulates miR-370 expression. miR-370 was also found downregulated in bladder carcinoma (Yoshino et al, 2011). These findings seem in conflict with the miR-370 in gastric cancers S-S Lo et al results of our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Interleukin-6 treatment downregulates miR-370 expression, while 5-aza-dC upregulates miR-370 expression. miR-370 was also found downregulated in bladder carcinoma (Yoshino et al, 2011). These findings seem in conflict with the miR-370 in gastric cancers S-S Lo et al results of our study.…”
Section: Discussioncontrasting
confidence: 84%
“…19 Our previous studies indicated that both miRNAs function as tumor suppressors that target multiple oncogenes. 12,20,21 Recent reports also indicated that miR-1 acts as a tumor suppressor in PCa by influencing multiple cancer-related processes and inhibiting cell proliferation and motility. 22 We also reported miR-145 downregulation in many types of human cancers, including PCa, suggesting that miR-145 functions as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we sequentially identified tumor suppressive miRNAs in several types of cancers, such as head and neck squamous cell carcinoma, 9,10 esophageal squamous cell carcinoma, 11 bladder cancer, 12,13 renal cell carcinoma 14 and PCa 15 and described the molecular pathways they regulate. Our analysis of miRNA-regulated cancer pathways provided novel insights for diagnostic and therapeutic strategies for these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that several miRNAs, such as miR-146a, miR-155, and miR-21, are involved in H. pylori-induced infection (23)(24)(25). MiR-370 has been verified as a tumor suppressor in bladder cancer and cholangiocarcinoma cell lines (26,27). Furthermore, FoxM1 is predicted as a putative target of miR-370 by bioinformatics.…”
Section: Introductionmentioning
confidence: 99%